PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV YANG MENGIKUTI DENGAN YANG TIDAK MENGIKUTI BIMBINGAN BELAJAR - Annisa, Annisa; Putra, Zetra Hainul; Kurniaman, Otang (Unversitas Katolik Santo Thomas, 2020)
The purpose of this study is to compare the learning outcomes of fourth grade students in elementary schools who take tutoring with students who do not take tutoring and find out the motivation of students to follow guidance. Categories of student learning outcomes with the motivation of students who take tutoring are evaluated from the very low, low, medium, high, and very high categories. The method used in this research is quantitative descriptive. This research was conducted on 98 students from a public elementary school in Pekanbaru. The instruments used to collect data are objective test questions on the material of flat shapes, statistics and angle measurements as well as questionnaires about students' motivation to follow tutoring. The results of this study indicate that the learning outcomes of students who take tutoring are better than students who do not follow tutoring, and the motivation of students who take tutoring is motivated because students' desire to obtain learning outcomes is increased and better understand the science of mathematics learned. The implication of this research is that parents need to consider their children to attend tutoring and schools need to think and design learning that can improve student learning outcomes.